Co-incubation of PMN and CaCo-2 cells modulates inflammatory potential - Schaefer, M. B.; Schaefer, C. A.; Hecker, M.; Morty, R. E.; Witzenrath, M.; Seeger, W.; Mayer, K. (Cellular and Molecular Biology, 2017)
Polymorphonuclear granulocytes (PMN) are activated in inflammatory reactions. Intestinal epithelial cells are relevant for maintaining the intestinal barrier. We examined interactions of PMN and intestinal epithelial cell-like CaCo-2 cells to elucidate their regulation of inflammatory signalling and the impact of cyclooxygenase (COX), nitric oxide (NO) and platelet-activating factor (PAF). Human PMN and CaCo-2 cells, separately and in co-incubation, were stimulated with the calcium ionophore A23187 or with N-Formyl-methionyl-leucyl-phenylalanin (fMLP) that activates PMN only. Human neutrophil elastase (HNE) and respiratory Burst were measured. To evaluate the modulation of inflammatory crosstalk we applied inhibitors of COX (acetyl salicylic acid; ASA), NO-synthase (N-monomethyl-L-arginin; L-NMMA), and the PAF-receptor (WEB2086). Unstimulated, co-incubation of CaCo-2 cells and PMN led to significantly reduced Burst and elevated HNE as compared to PMN. After stimulation with A23187, co-incubation resulted in an inhibition of Burst and HNE. Using fMLP co-incubation failed to modulate Burst but increased HNE. Without stimulation, all three inhibitors abolished the effect of co-incubation on Burst but did not change HNE. ASA partly prevented modulation of Burst L-NMMA and WEB2086 did not change Burst but abolished mitigation of HNE. Without stimulation, co-incubation reduced Burst and elevated HNE. Activation of PMN and CaCo-2 cells by fMLP as compared to A23187 resulted in a completely different pattern of Burst and HNE, possibly due to single vs. dual cell activation. Anti-inflammatory effect of co-incubation might in part be due to due to COX-signalling governing Burst whereas NO- and PAF-dependent signalling seemed to control HNE release.